The Effects of Economic Shocks on Heterogeneous Inflation Expectations - Chang, Yoosoon (IMF Working Papers; Working Paper ;, 2022)
In this paper, we examine how economic shocks affect the distribution of household inflation expectations. We show that the dynamics of households' expected inflation distributions are driven by three distinctive functional shocks, which influence the expected inflation distribution through disagreement, level shift and ambiguity. Linking these functional shocks to economic shocks, we find that contractionary monetary shocks increase the average level of inflation expectation with anchoring effects, with a reduction in disagreement and an increase in the share of households expecting future inflation to be between 2 to 4 percent. Such anchoring effects are not observed when the high inflation periods prior to the Volcker disinflation are included. Expansionary government spending shocks have inflationary effects on both short and medium-run inflation expectations, while an increase in personal income tax shocks is inflationary for mediumrun. A surprise increase in gasoline prices increases the level of inflation expectations, but lowers the share of households with 2 percent inflation expectations.